Interventions to improve adherence to treatment for paediatric tuberculosis in low- and middle-income countries: a systematic review and meta-analysis - Meaghann S Weaver; Knut Lönnroth; Scott C Howard; Debra L Roter; Catherine G Lam (The World Health Organization, 2015)
Abstract Objective To assess the design, delivery and outcomes of interventions to improve adherence to treatment for paediatric tuberculosis in low- and middle-income countries and develop a contextual framework for such interventions. Methods We searched PubMed and Cochrane databases for reports published between 1 January 2003 and 1 December 2013 on interventions to improve adherence to treatment for tuberculosis that included patients younger than 20 years who lived in a low- or middle-income country. For potentially relevant articles that lacked paediatric outcomes, we contacted the authors of the studies. We assessed heterogeneity and risk of bias. To evaluate treatment success - i.e. the combination of treatment completion and cure - we performed random-effects meta-analysis. We identified areas of need for improved intervention practices. Findings We included 15 studies in 11 countries for the qualitative analysis and of these studies, 11 qualified for the meta-analysis - representing 1279 children. Of the interventions described in the 15 studies, two focused on education, one on psychosocial support, seven on care delivery, four on health systems and one on financial provisions. The children in intervention arms had higher rates of treatment success, compared with those in control groups (odds ratio: 3.02; 95% confidence interval: 2.19-4.15). Using the results of our analyses, we developed a framework around factors that promoted or threatened treatment completion. Conclusion Various interventions to improve adherence to treatment for paediatric tuberculosis appear both feasible and effective in low- and middle-income countries.